PENGARUH DUKUNGAN MANAJEMEN PUNCAK DAN KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KESUKSESAN PENERAPAN SISTEM INFORMASI AKUNTANSI DAN KINERJA ORGANISASI PADA OPD PEMERINTAH KOTA/KABUPATEN DI WILAYAH PESISIR UTARA PROVINSI RIAU - Aulia Sakura; Fitrios Ruhul; Putra Agri Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aimed to examine the effect of top management support and human resource ability on the successful application of the accounting information system and organizational performance on regional apparatus organization in districts/cities in the northern coast. The sampling method using analysis and descriptive method. In this study the data needed all population sampled 104 regional apparatus organization. The data analysis used in the study was Smart PLS, while the data used was a questionnaire that had been filled in by each OPD. The results show that, top management support has an affects on the success of the accounting information system and has no affects on the organizational performance, ability human resources has an effect on the success of the accounting information system and organizational performance, the successful aplication accounting information system has an effect on organizational performance.Keywords : Top Management Support, Human Resources Ability, The Succesful Application Of The Accounting Information System, Organizational Performance.